Theoretical investigation of curved π‐conjugated fullerene flakes: open‐shell character, aromaticity, and third‐order nonlinear optical property†. (25th May 2016) - Fukuda, Kotaro; Fujiyoshi, Jun‐ya; Minamida, Yuka; Nagami, Takanori; Matsui, Hiroshi; Ito, Soichi; Kishi, Ryohei; Kitagawa, Yasutaka; Champagne, Benoît; Nakano, Masayoshi; Abe, Manabu; Sheridan, Robert S.
Abstract : Open‐shell singlet nature, aromaticity, and second hyperpolarizabilities of two kinds of curved π‐conjugated fragments of C60 fullerene, called C60 flakes, together with their corresponding planar analogues are theoretically investigated. It is found that one curved system, A-1, exhibitsintermediate open‐shell singlet nature, while the other structure, B-1, and the two corresponding planar systems possess a closed‐shell ground state. The variation of the open‐shell singlet nature is explained by the number of Clar's sextets in the resonance structures, which is associated with the local aromaticity, as quantified by the NICS0 values. The calculated orientationally averaged second hyperpolarizabilities show that theintermediate open‐shell singlet system A‐1 exhibits the best performance, and that the other curved system B‐1 is the worst among the four C60 flakes, whereas all systems exhibit better performance than the original spherical C60 system. This tendency suggests that a lower dimensionality in the π‐conjugated structure is beneficial to the construction of efficient nonlinear optical molecules. The present results not only show that the open‐shell singlet system A‐1 is a performant nonlinear optical molecule, but they also contribute to a deeper understanding of the electronic structure of curved π‐conjugated molecules. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Open‐shell singlet nature, aromaticity, and second hyperpolarizabilities of two kinds of curved π‐conjugated fragments of C60 fullerene, called C60 flakes, together with their corresponding planar analogues are theoretically investigated. It is found (i) that all C60 flakes present larger average static second hyperpolarizabilities ( γ s ) than C60 ; and (ii) that the curved A‐1 flake, having an intermediate diradical character, exhibits the largest γ s value, consistently with the y–γ correlation.